Projeto de promoção da sustentabilidade energética para jovens e crianças (projeto Smart2B) - Gerardo, F.; Gomes, D.; Filipe, I. (ICRE 2022 - 3rd Porto International Conference on Research in Education, 2022)
Project to promote energy sustainability for young people and children Authors: Filomena Gerardo, Diogo Gomes & Inês Filipe The SMART2B project, funded by the European Union, aims to improve the capacity of existing buildings through the development of sensors that act directly on what we currently call the “Internet of Things”. Its purpose is to control equipment while improving buildings' internal comfort and energy efficiency. SMART2B will follow a user-centric approach that simplifies the control of equipment and devices and provides information on total energy performance. This approach will enable the transition from passive buildings to active components of energy systems. Thus, being specifically adapted to the user's needs, the SMART2B project will provide new business models for the energy market associated with buildings, combining the savings of energy efficiency measures with the gains from the active contribution of buildings, through flexible services and exploring at the same time maximum your intelligence levels. SMART2B will include a suite of demonstrators divided by 5 pilots (14 buildings) in the Mediterranean, Central, and Northern European climates. The demonstrators aim to show the ease of integrating these solutions in different buildings. Santa Casa da Misericórdia de Lisboa, as an end-user partner, intends to develop an energy sustainability program with children (8 to 12 years old) and young people (16 to 21 years old), who will be encouraged to get involved in the sustainability theme, on which they will carry out various activities. It is expected that this project will promote sustainable and inclusive solutions, responding to the new challenges of environmental issues and also involving future generations in these themes of energy sustainability.